"Formation Of Architecture of Historical City Centers of Uzbekistan" (On the Example of the City of Bukhara) (Journal of Architectural Design, 2022)
This article describes the features of the formation of historical and modern architecture of Bukhara, analyzes the architectural features in the context of the development of historical architecture of the city, identifies trends in the development of ecological approaches. In modern construction, projects have been developed on the basis of extensive and scientific research on historical monuments of cultural heritage and samples and comparisons of new modern buildings. A number of examples of modern and historical construction of buildings in the historical environment of the city of Bukhara, research related to their description based on the impact on the perception of the integrity and authenticity of the architectural environment are analyzes